Secure and energy efficient optimal routing scheme for wireless sensor networks using IBFA and LDCSN-BSHHO algorithms - et. al., Edwin Rajesh.A, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensors networks (WSN) are very common because of their advancements in a big quantity of applications. The most vital design-goals aimed at WSN are energy efficiency in addition to secured Data Transmission (DT). This paper addresses the energy as well as security issues of the WSN and proposes a secure and energy-aware optimal routing scheme for WSN using learning of dynamic characteristics of sensor nodes with Bidirectional search based Harris Hawk optimizations (LDCSN-BSHHO). The proposed optimal routing is performed utilizing ‘4’ steps: i) clustering, ii) Cluster Heads (CH) selection, iii) data encryption, and iv) routing. Initially, to expand the Network Life-Time (NLT), the Weigh Utility-based Stratified Sampling (WUSS) method clusters the Sensor Nodes (SN). Next, the Elite Opposition and Ranking Mutation based Butterfly Optimization Algorithm (EORM-BOA) method optimally select the CH for the clusters. After that, an Improved Blowfish Algorithm (IBFA) encrypts the Data Packets (DP) to render data security. Finally, the LDCSN-BSHHO sent the encrypted DP to the Base Stations (BS) via the optimum path. It dynamically studies the node's behavior and selects an optimal path utilizing the BSHHO algorithm for data transfer. This kind of energy and security-centered method for WSN routing is labeled as secure and Energy-Aware Routing (EAR) of WSN. The proposed method’s outcomes are examined and weighed against the other prevailing techniques, which shows the proposed methods’ efficiency for optimal routing and the data’s security.